A high thermal conductivity ceramic material and its preparation method and application

Through specific raw material formulation and preparation process, high thermal conductivity ceramic materials are prepared, and combined with multi-layer structure design and intelligent temperature control system, the problems of insufficient thermal conductivity and high preparation cost of existing ceramic materials are solved, and efficient and intelligent heat dissipation effect is achieved, which is suitable for high-power electronic equipment.

CN119751029AInactive Publication Date: 2025-04-04HAINAN HENGRAN TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411936831.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing high-thermal conductivity ceramic materials still have problems such as limited thermal conductivity, complex preparation process and high cost in terms of heat dissipation of high-power electronic equipment.

Method used

Using specific raw material formulas, including germanate, rare earth oxides and high-purity alumina, high-thermal conductivity ceramic materials are prepared through modification treatment and conventional ceramic preparation processes, and combined with multi-layer structural design, microchannel structure and intelligent temperature control system to make efficient heat dissipation components.

Benefits of technology

It significantly improves the room temperature thermal conductivity of ceramic materials to reach no less than 250W/m·K, reduces the preparation cost, improves the heat dissipation efficiency, and realizes intelligent thermal management, which is suitable for long-term and high-load operation of high-power electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751029A_ABST
    Figure CN119751029A_ABST
Patent Text Reader

Abstract

The present invention provides a high thermal conductivity ceramic material and its preparation method and application. The material is composed of raw materials such as aluminum oxide, silicon nitride, silicon carbide, zirconium oxide, graphite, titanium boride, germanate, rare earth oxide additives and titanate coupling agents, and is prepared by modification, molding and sintering. It has excellent performance of thermal conductivity not less than 50W / m·K at room temperature. The ceramic material can be used to prepare heat dissipation materials, and is particularly suitable for thermal management of high-power electronic equipment or systems. The present invention also provides an efficient heat dissipation component made of the high thermal conductivity ceramic material, which adopts a multi-layer structure design, including a core heat dissipation layer and a high thermal conductivity metal layer, a microchannel structure is designed inside, a heat dissipation fin structure is designed on the surface, and an intelligent temperature control system is integrated to achieve efficient and stable heat dissipation performance. The high thermal conductivity ceramic material and its heat dissipation component of the present invention have broad application prospects in the field of thermal management of electronic equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of new materials, and specifically discloses a high thermal conductivity ceramic material and a preparation method and application thereof. Background Art

[0002] With the rapid development of modern electronic technology, the application of high-power electronic equipment is becoming more and more extensive, which puts higher requirements on heat dissipation materials. Although traditional heat dissipation materials, such as metals, alloys and some ceramic materials, can meet the heat dissipation needs to a certain extent, their heat dissipation performance is often insufficient in the face of high-power and high-density integrated electronic equipment. Although metal and alloy materials have high thermal conductivity, they have high density, high processing cost, and are prone to corrosion in certain specific environments; and although some ceramic materials have good high temperature resistance, their thermal conductivity is relatively low, which makes it difficult to meet the needs of efficient heat dissipation.

[0003] Especially for high-power electronic devices or systems, such as large servers, high-performance computing equipment, power electronic equipment, etc., the heat dissipation problem is particularly prominent. These devices generate a lot of heat when working. If they cannot be dissipated in time and effectively, it will cause the performance of the equipment to decline and even cause serious safety hazards.

[0004] Although the high thermal conductivity ceramic materials in the prior art have improved thermal conductivity to a certain extent, they still have many shortcomings. For example, the raw material formula is not optimized, resulting in limited thermal conductivity; the preparation process is complicated and the cost is high; and the heat dissipation component design is not reasonable, making it difficult to give full play to the heat dissipation performance of ceramic materials.

[0005] Therefore, there is an urgent need for a new type of high thermal conductivity ceramic material and a preparation method thereof, as well as a heat dissipation component based on the material, to meet the urgent demand for efficient heat dissipation of high-power electronic equipment. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a high thermal conductivity ceramic material and a preparation method and application thereof.

[0007] The present invention includes the following technical solutions:

[0008] A high thermal conductivity ceramic material, comprising the following raw materials by weight:

[0009]

[0010]

[0011] Furthermore, in the above-mentioned high thermal conductivity ceramic material, the germanate is selected from one of zinc germanate, sodium germanate or lithium germanate.

[0012] Furthermore, in the above-mentioned high thermal conductivity ceramic material, the rare earth oxide additive is selected from one or more of yttrium oxide, lanthanum oxide or cerium oxide.

[0013] Furthermore, in the above-mentioned high thermal conductivity ceramic material, the purity of the aluminum oxide is not less than 99%, and the average particle size is controlled at 0.5-5 microns.

[0014] Furthermore, the above-mentioned high thermal conductivity ceramic material has a thermal conductivity of not less than 250 W / m·K at room temperature.

[0015] The above-mentioned method for preparing a high thermal conductivity ceramic material comprises the following steps:

[0016] (i) Modification treatment: before the raw materials are mixed, the titanate coupling agent is uniformly coated on the surface of silicon nitride and silicon carbide particles, and heat treated at 100-150° C. for 1-3 hours to enhance the interfacial bonding force between the particles and the overall performance of the ceramic material;

[0017] (ii) Molding: According to conventional ceramic preparation processes, the modified raw materials are mixed with other raw materials, refined, dried, granulated, and pressed into shape;

[0018] (iii) Sintering: The green body after forming is subjected to high-temperature sintering in an inert gas protective atmosphere such as nitrogen or argon. The sintering temperature is controlled at 1600-1800° C., and the green body is naturally cooled after being kept at this temperature for 3-6 hours to obtain the high thermal conductivity ceramic material.

[0019] Furthermore, in the above method for preparing a high thermal conductivity ceramic material, the step (ii) comprises the following specific steps:

[0020] (a) Mixing: The modified raw material and other raw materials are accurately weighed according to a predetermined ratio, and mixed and refined using a ball mill. The ball milling time is 12-24 hours, and the ball milling medium is zirconia beads;

[0021] (b) Drying: Place the mixed and refined raw materials in a drying oven, set the drying temperature to 80-120°C, and the drying time to 6-18 hours;

[0022] (c) granulation: adding a polyvinyl alcohol solution accounting for 3% of the total weight of the powder as a binder to the dried raw material, performing granulation treatment to obtain a uniform granular ceramic raw material;

[0023] (d) Compression molding: Using a compression molding device, the granulated raw material is pressed and molded at a pressure of 10-50 MPa for a holding time of 5-30 hours to obtain a ceramic green body of a desired shape.

[0024] The invention discloses the application of the high thermal conductivity ceramic material in preparing heat dissipation materials, in particular, in heat dissipation components of high-power electronic equipment or systems.

[0025] The present invention also discloses a high-efficiency heat dissipation component made of a high thermal conductivity ceramic material, wherein the high-efficiency heat dissipation component is used for thermal management of high-power electronic equipment or systems, wherein:

[0026] (1) The high thermal conductivity ceramic material is prepared according to the method of claim 6, and has a thermal conductivity of not less than 250 W / m·K at room temperature;

[0027] (2) The heat dissipation component adopts a multi-layer structure design, including at least one core heat dissipation layer made of the high thermal conductivity ceramic material, and high thermal conductivity metal layers, such as copper or aluminum layers, attached to the upper and lower surfaces of the core heat dissipation layer, which are tightly combined by welding or bonding technology;

[0028] (3) A microchannel structure is designed inside the core heat dissipation layer to accommodate and guide the circulation of the coolant. The coolant is water, ethylene glycol or other high thermal conductivity liquids, and the circulation is driven by a micropump system;

[0029] (4) The surface of the heat dissipation component is designed with a precise heat dissipation fin structure to increase the heat dissipation area. At the same time, air convection channels are formed between the fins to optimize the natural convection or forced convection heat dissipation effect;

[0030] (5) The heat dissipation component integrates an intelligent temperature control system that can monitor and adjust parameters such as the coolant circulation speed and the fan speed of the heat dissipation fins in real time, and automatically adjust the heat dissipation strategy according to the working status of the electronic equipment or system to ensure efficient and stable heat dissipation performance.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] First, through a carefully designed raw material formula and a unique preparation method, the present invention successfully prepares a high thermal conductivity ceramic material, whose thermal conductivity at room temperature is not less than 250W / m·K, which is significantly better than traditional ceramic materials and some metal materials, and provides a solid material basis for efficient heat dissipation. Secondly, the preparation method of the present invention is simple in process and low in cost. The interface bonding force between particles is enhanced by modification treatment, and the overall performance of the ceramic material is improved. At the same time, the conventional ceramic preparation process is used for molding and sintering, which is easy to realize large-scale industrial production. Furthermore, the high-efficiency heat dissipation component made of the high thermal conductivity ceramic material adopts a multi-layer structure design, combines a high thermal conductivity metal layer and a microchannel structure, and a precise heat dissipation fin structure, which greatly improves the heat dissipation efficiency and ensures the stable performance of high-power electronic equipment or systems under long-term and high-load operation. In addition, the heat dissipation component also integrates an intelligent temperature control system, which can adjust the heat dissipation strategy in real time according to the working state of the equipment, and realizes intelligent and precise thermal management. In summary, the present invention not only provides an efficient and reliable heat dissipation solution for high-power electronic equipment, but also promotes the development and progress of heat dissipation materials and technologies, and has broad application prospects and significant economic and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 Comparison of thermal conductivity (W / (m·K) of ceramics in the test examples;

[0034] Figure 2 Comparison of the compressive strength (Mpa) of the ceramics in the test examples;

[0035] Figure 3 Comparison of the flexural strength (Mpa) of the ceramics in the test examples. DETAILED DESCRIPTION

[0036] A high thermal conductivity ceramic material, comprising the following raw materials by weight:

[0037]

[0038] The germanate is selected from zinc germanate, sodium germanate or lithium germanate;

[0039] The rare earth oxide additive is selected from one or more of yttrium oxide, lanthanum oxide or cerium oxide;

[0040] The purity of the aluminum oxide is not less than 99%, and the average particle size is controlled at 0.5-5 microns;

[0041] The method for preparing the above-mentioned high thermal conductivity ceramic material comprises the following steps:

[0042] (i) Modification treatment: before mixing the raw materials, the titanate coupling agent is evenly coated on the surface of silicon nitride and silicon carbide particles, and heat treated at 120° C. for 2 h to enhance the interfacial bonding force between the particles and the overall performance of the ceramic material;

[0043] (ii) Molding: According to conventional ceramic preparation processes, the modified raw materials are mixed with other raw materials, refined, dried, granulated, and pressed into shape;

[0044] (iii) Sintering: The green body after forming is subjected to high-temperature sintering in an inert gas protection atmosphere such as nitrogen or argon. The sintering temperature is controlled at 1700° C. and the green body is naturally cooled after being kept at this temperature for 4.5 hours to obtain the high thermal conductivity ceramic material.

[0045] The step (ii) comprises the following specific steps:

[0046] (a) Mixing: The modified raw material and other raw materials are accurately weighed according to a predetermined ratio, and mixed and refined using a ball mill. The ball milling time is 16 h, and the ball milling medium is zirconia beads;

[0047] (b) Drying: Place the mixed and refined raw materials in a drying oven, set the drying temperature to 100°C, and the drying time to 10 hours;

[0048] (c) granulation: adding a polyvinyl alcohol solution accounting for 3% of the total weight of the powder as a binder to the dried raw material, performing granulation treatment to obtain a uniform granular ceramic raw material;

[0049] (d) Compression molding: The granulated raw material is pressed and molded at a pressure of 25 MPa using a compression molding device, with a holding time of 15 h to obtain a ceramic green body of the desired shape.

[0050] The titanate coupling agent was purchased from Wuhan Chengtian Fine Chemical Co., Ltd. (isopropyl tri(dioctylphosphoyl) titanate).

[0051] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0052] Example 1

[0053] A high thermal conductivity ceramic material, comprising the following raw materials by weight:

[0054]

[0055] The germanate is selected from zinc germanate;

[0056] The rare earth oxide additive is selected from yttrium oxide;

[0057] The purity of the aluminum oxide is not less than 99%, and the average particle size is controlled at 0.5-5 microns;

[0058] The method for preparing the above-mentioned high thermal conductivity ceramic material comprises the following steps:

[0059] (i) Modification treatment: before mixing the raw materials, the titanate coupling agent is evenly coated on the surface of silicon nitride and silicon carbide particles, and heat treated at 120° C. for 2 h to enhance the interfacial bonding force between the particles and the overall performance of the ceramic material;

[0060] (ii) Molding: According to conventional ceramic preparation processes, the modified raw materials are mixed with other raw materials, refined, dried, granulated, and pressed into shape;

[0061] (iii) Sintering: The green body after forming is subjected to high-temperature sintering in an inert gas protection atmosphere such as nitrogen or argon. The sintering temperature is controlled at 1700° C. and the green body is naturally cooled after being kept at this temperature for 4.5 hours to obtain the high thermal conductivity ceramic material.

[0062] The step (ii) comprises the following specific steps:

[0063] (a) Mixing: The modified raw material and other raw materials are accurately weighed according to a predetermined ratio, and mixed and refined using a ball mill. The ball milling time is 16 h, and the ball milling medium is zirconia beads;

[0064] (b) Drying: Place the mixed and refined raw materials in a drying oven, set the drying temperature to 100°C, and the drying time to 10 hours;

[0065] (c) granulation: adding a polyvinyl alcohol solution accounting for 3% of the total weight of the powder as a binder to the dried raw material, performing granulation treatment to obtain a uniform granular ceramic raw material;

[0066] (d) Compression molding: The granulated raw material is pressed and molded at a pressure of 25 MPa using a compression molding device, with a holding time of 15 h to obtain a ceramic green body of the desired shape.

[0067] Example 2

[0068] A high thermal conductivity ceramic material, comprising the following raw materials by weight:

[0069] Alumina 50 parts

[0070] Silicon nitride 20 parts

[0071] Silicon carbide 15 parts

[0072] Zirconium oxide 7.5 parts

[0073] 3.5 parts of graphite

[0074] 2 parts of titanium boride

[0075] 1.5 parts of Germanate

[0076] Rare earth oxide additive: 1.5 parts

[0077] Titanate coupling agent: 1 part.

[0078] The germanate is selected from sodium germanate;

[0079] The rare earth oxide additive is selected from lanthanum oxide;

[0080] The purity of the aluminum oxide is not less than 99%, and the average particle size is controlled at 0.5-5 microns;

[0081] The method for preparing the above-mentioned high thermal conductivity ceramic material comprises the following steps:

[0082] (i) Modification treatment: before mixing the raw materials, the titanate coupling agent is evenly coated on the surface of silicon nitride and silicon carbide particles, and heat treated at 120° C. for 2 h to enhance the interfacial bonding force between the particles and the overall performance of the ceramic material;

[0083] (ii) Molding: According to conventional ceramic preparation processes, the modified raw materials are mixed with other raw materials, refined, dried, granulated, and pressed into shape;

[0084] (iii) Sintering: The green body after forming is subjected to high-temperature sintering in an inert gas protection atmosphere such as nitrogen or argon. The sintering temperature is controlled at 1700° C. and the green body is naturally cooled after being kept at this temperature for 4.5 hours to obtain the high thermal conductivity ceramic material.

[0085] The step (ii) comprises the following specific steps:

[0086] (a) Mixing: The modified raw material and other raw materials are accurately weighed according to a predetermined ratio, and mixed and refined using a ball mill. The ball milling time is 16 h, and the ball milling medium is zirconia beads;

[0087] (b) Drying: Place the mixed and refined raw materials in a drying oven, set the drying temperature to 100°C, and the drying time to 10 hours;

[0088] (c) granulation: adding a polyvinyl alcohol solution accounting for 3% of the total weight of the powder as a binder to the dried raw material, performing granulation treatment to obtain a uniform granular ceramic raw material;

[0089] (d) Compression molding: The granulated raw material is pressed and molded at a pressure of 25 MPa using a compression molding device with a holding time of 15 h to obtain a ceramic green body of the desired shape.

[0090] Example 3

[0091] A high thermal conductivity ceramic material, comprising the following raw materials by weight:

[0092]

[0093]

[0094] The germanate is selected from lithium germanate;

[0095] The rare earth oxide additive is selected from cerium oxide;

[0096] The purity of the aluminum oxide is not less than 99%, and the average particle size is controlled at 0.5-5 microns;

[0097] The method for preparing the above-mentioned high thermal conductivity ceramic material comprises the following steps:

[0098] (i) Modification treatment: before mixing the raw materials, the titanate coupling agent is evenly coated on the surface of silicon nitride and silicon carbide particles, and heat treated at 120° C. for 2 h to enhance the interfacial bonding force between the particles and the overall performance of the ceramic material;

[0099] (ii) Molding: According to conventional ceramic preparation processes, the modified raw materials are mixed with other raw materials, refined, dried, granulated, and pressed into shape;

[0100] (iii) Sintering: The green body after forming is subjected to high-temperature sintering in an inert gas protection atmosphere such as nitrogen or argon. The sintering temperature is controlled at 1700° C. and the green body is naturally cooled after being kept at this temperature for 4.5 hours to obtain the high thermal conductivity ceramic material.

[0101] The step (ii) comprises the following specific steps:

[0102] (a) Mixing: The modified raw material and other raw materials are accurately weighed according to a predetermined ratio, and mixed and refined using a ball mill. The ball milling time is 16 h, and the ball milling medium is zirconia beads;

[0103] (b) Drying: Place the mixed and refined raw materials in a drying oven, set the drying temperature to 100°C, and the drying time to 10 hours;

[0104] (c) granulation: adding a polyvinyl alcohol solution accounting for 3% of the total weight of the powder as a binder to the dried raw material, performing granulation treatment to obtain a uniform granular ceramic raw material;

[0105] (d) Compression molding: The granulated raw material is pressed and molded at a pressure of 25 MPa using a compression molding device, with a holding time of 15 h to obtain a ceramic green body of the desired shape.

[0106] Comparative Example 1

[0107] Same as Example 2, except that the modification step of the titanate coupling agent is not included.

[0108] Comparative Example 2

[0109] Same as Example 2, but without germanate.

[0110] Comparative Example 3

[0111] Same as Example 2, but without the rare earth oxide additive.

[0112] Comparative Example 4

[0113] Same as Example 2, but without rare earth oxide additive and germanate.

[0114] Comparative Example 5

[0115] Common thermal conductive ceramic materials available on the market.

[0116] Test Case

[0117] 1 The thermal conductivity measurement of high thermal conductivity ceramics follows the GB / T 39862-2021 "Testing of thermal conductivity of high thermal conductivity ceramics" standard, which is designed for homogeneous ceramic materials with a thermal conductivity greater than 20W / (m·K) at room temperature and an apparent porosity less than 0.2%.

[0118] During the measurement process, the test instrument includes a steady-state thermal conductivity tester that calculates the thermal conductivity by measuring the heat flow under a stable temperature gradient.

[0119] The thermal conductivities of the ceramics of Examples 1-3 and Comparative Examples 1-5 were measured.

[0120] 2At the same time, the strength determination of high thermal conductivity ceramics follows the national standards GB / T 6569-2006 "Test Method for Bending Strength of Fine Ceramics" and GB / T 4741-2008 "Test Method for Compressive Strength of Ceramic Materials". During the determination process, a universal material testing machine is used as the core testing instrument, which can accurately apply force and record the deformation and rupture of the sample during the force process. For the test of bending strength, the three-point bending method is used to record the maximum load when the sample breaks, and the bending strength is calculated based on this, expressed in MPa (megapascals). For the test of compressive strength, the direct compression method is used, and the maximum load when the sample breaks is also recorded, and the compressive strength is calculated, and the unit is also MPa.

[0121] The flexural strength and compressive strength of Examples 1-3 and Comparative Examples 1-5 were measured.

[0122] The above test results are shown in Table 1 and Figure 1-3 shown.

[0123] Table 1 Thermal conductivity and mechanical strength of high thermal conductivity ceramics

[0124]

[0125]

[0126] From the comparison between Examples 1-3 and Comparative Example 5, it can be seen that the high thermal conductivity ceramics prepared by the present invention are higher than the common thermal conductive ceramics on the market in terms of both thermal conductivity and mechanical strength, and the raw materials of the present invention are easily available, the preparation is simple, the cost is low, and it has good market competitiveness. From the comparison between Example 2 and Comparative Example 1, it can be seen that the use of titanate coupling agent on the surface of silicon nitride and silicon carbide particles can effectively improve the thermal conductivity and compressive strength of the ceramics; from the comparison between Example 2 and Comparative Examples 2-4, it can be found that the addition of germanate forms a synergistic effect with the rare earth oxide additives, and jointly improves the overall performance and thermal conductivity of the ceramic material.

[0127] From the above examples, it can be seen that the present invention has successfully prepared a high thermal conductivity ceramic material, whose thermal conductivity at room temperature is not less than 250W / m·K, which is significantly better than traditional ceramic materials and some metal materials, and provides a solid material basis for efficient heat dissipation. Secondly, the preparation method of the present invention is simple in process and low in cost. The interface bonding force between particles is enhanced through modification treatment, and the overall performance of the ceramic material is improved. At the same time, conventional ceramic preparation processes are used for molding and sintering, which is easy to realize large-scale industrial production.

[0128] The above are limited to several preferred embodiments of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A high thermal conductivity ceramic material, characterized in that: The following raw materials are included by weight:

2. A high thermal conductivity ceramic material according to claim 1, characterized in that: The germanate is selected from zinc germanate, sodium germanate or lithium germanate.

3. A high thermal conductivity ceramic material according to claim 1, characterized in that: The rare earth oxide additive is selected from one or more of yttrium oxide, lanthanum oxide or cerium oxide.

4. The high thermal conductivity ceramic material according to claim 1, characterized in that: The purity of the aluminum oxide is not less than 99%, and the average particle size is controlled at 0.5-5 microns.

5. The high thermal conductivity ceramic material according to claim 1, characterized in that: The thermal conductivity of the ceramic material at room temperature is not less than 250 W / m·K.

6. The method for preparing a high thermal conductivity ceramic material according to any one of claims 1 to 5, characterized in that: The following steps are involved: (i) Modification treatment: before the raw materials are mixed, the titanate coupling agent is uniformly coated on the surface of silicon nitride and silicon carbide particles, and heat treated at 100-150° C. for 1-3 hours to enhance the interfacial bonding force between the particles and the overall performance of the ceramic material; (ii) Molding: According to conventional ceramic preparation processes, the modified raw materials are mixed with other raw materials, refined, dried, granulated, and pressed into shape; (iii) Sintering: The green body after forming is subjected to high-temperature sintering in an inert gas protective atmosphere such as nitrogen or argon. The sintering temperature is controlled at 1600-1800° C., and the green body is naturally cooled after being kept at this temperature for 3-6 hours to obtain the high thermal conductivity ceramic material.

7. The method for preparing a high thermal conductivity ceramic material according to claim 6, characterized in that: The step (ii) comprises the following specific steps: (a) Mixing: The modified raw material and other raw materials are accurately weighed according to a predetermined ratio, and mixed and refined using a ball mill. The ball milling time is 12-24 hours, and the ball milling medium is zirconia beads; (b) Drying: Place the mixed and refined raw materials in a drying oven, set the drying temperature to 80-120°C, and the drying time to 6-18 hours; (c) granulation: adding a polyvinyl alcohol solution accounting for 3% of the total weight of the powder as a binder to the dried raw material, performing granulation treatment to obtain a uniform granular ceramic raw material; (d) Compression molding: Using a compression molding device, the granulated raw material is pressed and molded at a pressure of 10-50 MPa for a holding time of 5-30 hours to obtain a ceramic green body of a desired shape.

8. Use of the high thermal conductivity ceramic material according to any one of claims 1 to 5 in the preparation of heat dissipation materials.

9. An efficient heat dissipation component made of high thermal conductivity ceramic material, characterized in that: The high-efficiency heat dissipation component is used for thermal management of high-power electronic equipment or systems, wherein: (1) The high thermal conductivity ceramic material is prepared according to the method of claim 6, and has a thermal conductivity of not less than 50 W / m·K at room temperature; (2) The heat dissipation component adopts a multi-layer structure design, including at least one core heat dissipation layer made of the high thermal conductivity ceramic material, and high thermal conductivity metal layers, such as copper or aluminum layers, attached to the upper and lower surfaces of the core heat dissipation layer, which are tightly combined by welding or bonding technology; (3) A microchannel structure is designed inside the core heat dissipation layer to accommodate and guide the circulation of the coolant. The coolant is water, ethylene glycol or other high thermal conductivity liquid, and the circulation is driven by a micropump system; (4) The surface of the heat dissipation component is designed with a precise heat dissipation fin structure to increase the heat dissipation area. At the same time, air convection channels are formed between the fins to optimize the natural convection or forced convection heat dissipation effect; (5) The heat dissipation component integrates an intelligent temperature control system that can monitor and adjust parameters such as the coolant circulation speed and the fan speed of the heat dissipation fins in real time, and automatically adjust the heat dissipation strategy according to the working status of the electronic equipment or system to ensure efficient and stable heat dissipation performance.